Notes sur la géologie et la paléontologie du Miocène de Lisbonne. XXI Primeira caracterização de dinoflagelados dos níveis mais baixos da série miocénica de Lisboa - Pais, João (2008)
This is the first report on Dinoflagellata from lowermost Miocene beds in Portugal (Tagus basin, Lisbon region, exposure at Benfica). Some general data about Dinoflagellata are presented. Descriptions are provided for some forms: Gonyaulacysta tenuitabulata, Spiniferites ramosus, Achomosphaera sp., Hystrichokolpoma rigaudae, Homotriblium cf. pallidum, Cordosphaeridium sp, and Lingulodinium machaerophorum. Lithostratigraphical study of an important section along Circular highway at Benfica has shown that there is a hitherto unknown sedimentary cycle in Lisbon's lowermost Miocene (upper Oligocene?). Pollen and Ostracoda point out to an Lower Aquitanian or even Upper Chattian age for the first Neogene marine transgression in Portugal, previously considered as Upper Aquitanian or Lower Burdigalian.